Construction of Contempt of Court Regulation in Indonesia - Siti Rahmawati Djula; Fence M. Wantu; Dian Ekawaty Ismail (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the Reconstruction of Contempt of Court Regulations in Indonesia. Contempt of court is defined as an act of contempt against the judiciary. In Indonesia, the meaning of contempt of court is only interpreted narrowly so that it is considered less inclusive of all judicial organizers. This type of research is normative legal research with a legislative, conceptual, comparative and case approach. The results of the study are that the position of the contempt of court regulation in Indonesia has been contained in a chapter in the latest Criminal Code, but its application has not been supported by formal procedures. The meaning of contempt of court in Indonesia is only interpreted narrowly, this can be seen in the latest Padal 281 of the Criminal Code which only seems to protect judges, the contempt of court regulation should also protect all judicial organizers who are directly involved in a judicial process, namely the prosecutor, legal representatives, victims, witnesses, and all trial participants. Next, contempt of court in Indonesia also only accommodates criminal contempt and sets aside civil contempt so that there is no deterrent effect for people, officials and others who do not comply with judicial decisions. Therefore, there is a need for special arrangements related to contempt of court in Indonesia that regulate crimes (criminal contempt) and non-compliance with court orders (civil contempt).